A política indigenista no Amazonas e o serviço de proteção aos índios: 1910-1932 - (:unkn) unknown (Universidade Federal do Amazonas, 2007)
This work intends to make a sociological analysis of the action of the Indigenous Protection Service (Serviço de Proteção aos Índios SPI), in the State of Amazonas, during the 1910-1932 period. Based on such concepts as devices, field and tutelary power we have tried not only to make a historical timetable of the presence of SPI in the State of Amazonas, but also to shed some light on the practices carried out by the indigenist body in the mission of conducting the Indian population in the region under its jurisdiction, of a primitive condition to a positive state , through a localled civilizatory process . The major objective is to bring to date critical reflections on these positivistic assumptions which have deeply marked the actions by the indigenist bodies (SPI, FUNAI). It is our intention in this dissertation, to show all the nuances of the rondonistic practices in the State of Amazonas during the first decades of the XX century.
Keywords: Política indigenista; Brasil - Serviços de Proteção aos Índios - História; Povos Indígenas; Indigenist politics; Indigenist people; OUTROS